2020
DOI: 10.3389/fcell.2020.564641
|View full text |Cite
|
Sign up to set email alerts
|

Altered Insulin Receptor Substrate 1 Phosphorylation in Blood Neuron-Derived Extracellular Vesicles From Patients With Parkinson’s Disease

Abstract: IntroductionDiabetes increases the risk of Parkinson’s disease (PD). The phosphorylation of type 1 insulin receptor substrate (IRS-1) determines the function of insulin signaling pathway. Extracellular vesicles (EVs) are emerging as biomarkers of human diseases. The present study investigated whether PD patients exert altered phosphorylation IRS-1 (p-IRS-1) inside the blood neuron-derived extracellular vesicles (NDEVs).Research Design and MethodsIn total, there were 94 patients with PD and 63 healthy controls … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 50 publications
0
14
0
Order By: Relevance
“…A high prevalence of insulin resistance was identified in a sample of 154 non-diabetic PD patients, with 58% being insulin-resistant as indicated by abnormal Homeostatic Model Assessment for Insulin Resistance (HOMA-IR) scores [ 157 ]. Dysfunctional brain insulin signaling has been shown using blood-neuron-derived extracellular vesicles, whereby PD patients display altered IRS1 phosphorylation, which is further correlated with tremor severity [ 158 ]. Despite the link, the role of insulin abnormalities in PD remains contentious, with little difference found between patients with PD and healthy controls in peripheral insulin resistance, quantified using a hyperinsulinemic-euglycemic clamp [ 71 ].…”
Section: Role Of Insulin In Ad and Pdmentioning
confidence: 99%
“…A high prevalence of insulin resistance was identified in a sample of 154 non-diabetic PD patients, with 58% being insulin-resistant as indicated by abnormal Homeostatic Model Assessment for Insulin Resistance (HOMA-IR) scores [ 157 ]. Dysfunctional brain insulin signaling has been shown using blood-neuron-derived extracellular vesicles, whereby PD patients display altered IRS1 phosphorylation, which is further correlated with tremor severity [ 158 ]. Despite the link, the role of insulin abnormalities in PD remains contentious, with little difference found between patients with PD and healthy controls in peripheral insulin resistance, quantified using a hyperinsulinemic-euglycemic clamp [ 71 ].…”
Section: Role Of Insulin In Ad and Pdmentioning
confidence: 99%
“…On the hand, diabetes is a well-known risk factor for PD [ 55 ], and poor glucose control is a predictor of rapid disease progression [ 56 ]. Insulin resistance triggers the significant PD pathogeneses, namely mitochondrial dysfunction and α-synuclein accumulation, and neuronal insulin resistance is remarkable in PwP [ 57 , 58 ]. Tamtaji et al demonstrated that probiotic treatment resulted in a reduction in inflammation (assessed by a high-sensitivity C-reactive protein test) and oxidative stress (assessed by glutathione levels) and an increase in insulin sensitivity [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…The levels of other plasma exosomal proteins, as the prion protein, apolipoprotein J (APOJ), ApoA1, CR1 subcomponent, cytokines, insulin receptor substrate 1 and proteasome complex proteins and several immunologic‐associated EVs surface markers, were also capable to distinguish PD cases from controls, while no differences were found for neurofilament light chain or BDNF levels (Anastasi et al, 2021; Chan et al, 2021; Chou et al, 2020; Chung, Chan, et al, 2020; Chung, Huang, et al, 2020; Kitamura et al, 2018; Leng et al, 2020; Vacchi et al, 2020; Vacchi et al, 2021). It was likewise reported that the levels of plasma NDEVs were increased in PD when compared with Controls (Ohmichi et al, 2019).…”
Section: Evs and Clinical Research On Neurodegenerative Disordersmentioning
confidence: 99%